The Mobilisation of Native Canadians During the Second World War - Stevenson, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1996)
AbstractHistorians have paid scant attention to the compulsory conscription of men under the National Resources Mobilisation Act (NRMA) in Canada during the Second World War. This paper uses the mobilisation of Native Canadians as a case-study to determine the depth and extent of human resource mobilisation policies between 1940 and 1945. Government mobilisation departments and agencies relied on a remarkably decentralised and permissive administrative structure to carry out the NRMA mobilisation mandate. These organizational traits were exacerbated by active Native Canadian opposition to conscription and other factors, such as the geographic isolation and poor health of many Native men. As a result, a patchwork of disparate, inconsistent and ineffectual mobilisation policies affecting Canadian Indians was adopted during the course of the war.